Estimating the Impact of Science Literacy Ability towards Problem Solving Ability of Junior High School Students - Amala, Inggrid Ayu; Sudarti, Sudarti; Handayani, Rif’ati Dina (FKIP Universitas Lampung, 2022)
Science learning has concepts related to phenomena that occur in nature. Therefore, students must be able to understand science in its entirety with scientific literacy activities and students will be able to learn science more easily by increasing their problem-solving abilities. This study aims to determine whether or not scientific literacy has an effect on problem solving abilities. This research is an experimental research with simple linear regression analysis method. Using class 8 odd semesters with a total of 29 students and the tests used are scientific literacy tests and problem solving tests. The result of this research is that the highest scientific literacy criteria is sufficient criteria with a percentage of 57.14% and indicators identify valid scientific opinions with the highest percentage. Meanwhile, in problem solving ability, the highest criteria are very good criteria, namely 62.06% and the highest indicator is an indicator of understanding the problem. Regression analysis stated that the significance value was 0.000 <0.05. Thus, there is an influence of scientific literacy (X) on problem solving ability (Y). Keywords: Scienctific literacy, problem solving ability, simple linier regression. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp661-669